2005
DOI: 10.3171/jns.2005.102.6.1122
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of secondary generalization of limbic seizures by stimulation of subthalamic nucleus in rats

Abstract: Unilateral STN DBS showed significant suppression of the secondary generalization of limbic seizures. Note, however, that SNR DBS was less effective, which implies that in addition to the nigral control of the epilepsy system, another antiepileptic mechanism such as antidromic stimulation of the corticosubthalamic pathway should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…Dinner, 2002Shon et al, 2004;Usui et al, 2005). The effect of DBS of the STN is presumably to induce local inhibition in the STN, which in turn reduces excitatory input to the SNr.…”
Section: Discussionmentioning
confidence: 99%
“…Dinner, 2002Shon et al, 2004;Usui et al, 2005). The effect of DBS of the STN is presumably to induce local inhibition in the STN, which in turn reduces excitatory input to the SNr.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also suggested that STN DBS could be useful in the treatment of epilepsy in animal mod-els (Usui et al, 2005) as well as in human (Chabardes et al, 2002;Lee et al, 2006). It consists of delivering electrical pulses within the STN through an implanted electrode connected to an implanted pulse generator (IPG) .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast Usui et al 75 found no treatment effect when they tested SNr DBS in rats with kainic acid-induced seizures. They compared a group of rats with a unilateral SNr electrode to a a group with a unilateral STN electrode.…”
Section: Stimulation Of the Stn And Snrmentioning
confidence: 96%
“…36,49,62,67,75,90,91 Animal epilepsy models have utilized pentylenetetrazol, kainic acid, bicuculline, picrotoxin, and kindling to induce seizures. 36,49,57,62,67,75,91 Sinusoidal AC versus DC stimulation protocols, synaptic versus nonsynaptic inhibition, regional alterations in neurochemistry, and different anatomic targets are among the many variables investigated in these models. 36,49,62,91 Finding effective targets for modulating epileptiform activity is arguably the most important, but most elusive variable in the quest to treat seizures with DBS.…”
Section: Animal Studiesmentioning
confidence: 99%